IMPROVISATION OF FURNACE FOR FORGING OPERATIONS IN TECHNICAL COLLEGES IN RIVERS STATE:IMPLICATION FOR VOCATIONAL COUNSELLING IN NIGERIA - Isaac, Ogundu,; Morgan, Amakiri Gloria; Ngozi, Ibeawuchi (European Scientific Journal, ESJ, 2015)
The purpose of this research was to develop an improvised furnace to enhance students’ performance in forging operations in technical colleges in Rivers State. The study adopted research and development design. Forging is the art of shaping metals by hammering. Man has known this art since ancient times. Today machines have largely replaced the sweat and muscle of the blacksmith, who nevertheless remains indispensable for carrying out the jobs done by hand, necessary in steel and engineering works. The furnace was found to be valid for forging at 4.00 and reliable using steel with molybdenum at hardness of 164 HRC. Any temperature and harder having melting points above 8500c and 164 HRC respectively may be inserted directly into the flaming charcoal. The improvised furnace is a teaching material that is made up of a steel vessel hardened with carbon – molybdenum in the ratio of 0.20:0.68 percent respectively. It was lined with bricks and fired with charcoal, using an electric blower connected to a low voltage generator. This furnace was used to carry out various forging operations. Based on the findings of this study, the researchers recommended the government; technical college principals and relevant agencies should provide funds to procure the materials and components for designing and constructing these furnaces by the teacher for teaching forging in Technical Colleges in Rivers State. Also, constant power supply, generators, accumulators, anvils, steel vessels, pipes and electric blowers should be provided and distributed by the ministry of education to the Technical Colleges for construction of furnaces for effective teaching of forging in Rivers State. The industries, government, non-governmental agencies and private enterprises and communities should provide components and consumable materials necessary for teaching. These materials should be supplied directly to the individual Technical Colleges in Rivers State. Vocational counselors should guide students to take up occupation in forging.